Disentangling the relationship between children’s motor ability, executive function and academic achievement - Schmidt, Mirko (PLoS One, 2017)
Even though positive relations between children’s motor ability and their academic achievement are frequently reported, the underlying mechanisms are still unclear. Executive function has indeed been proposed, but hardly tested as a potential mediator. The aim of the present study was therefore to examine the mediating role of executive function in the relationship between motor ability and academic achievement, also investigating the individual contribution of specific motor abilities to the hypothesized mediated linkage to academic achievement. At intervals of ten weeks, 236 children aged between 10 and 12 years were tested in terms of their motor ability (t1: cardiovascular endurance, muscular strength, motor coordination), core executive functions (t2: updating, inhibition, shifting), and academic achievement (t3: mathematics, reading, spelling). Structural equation modelling revealed executive function to be a mediator in the relation between motor ability and academic achievement, represented by a significant indirect effect. In separate analyses, each of the three motor abilities were positively related to children’s academic achievement. However, only in the case of children’s motor coordination, the mediation by executive function accounted for a significance percentage of variance of academic achievement data. The results provide evidence in support of models that conceive executive function as a mechanism explaining the relationship that links children’s physical activity-related outcomes to academic achievement and strengthen the advocacy for quality physical activity not merely focused on health-related physical fitness outcomes, but also on motor skill development and learning.